Development of E-Learning Chemistry Learning SMA / MA Based on Project based learning on Salt Hydrolysis Material Using the Flipped Classroom Approach in Class XI Senior High School - Lutfiah Azmi; Nurbaiti Nurbaiti; Rosena Putri Nabila; Novi Indriani; Ayu Wahyuni (Center For Advanced Material Processing, Artificial Intelligence, Biophys-Informatics (CAMPBIOTICS), Universitas Negeri Padang, 2021)
This study aims to produce saline hydrolysis elearning based on the project based learning learning model and assisted with the zainulteam.id LMS moddle and to reveal the validity and practicality of the e-learning. This type of research is research and development (R&D), the method used in this research is a development model using a 4-D design. They define, design, develop and disseminate. This research is limited to the development stage, validity and practicality tests. The data collection instrument was in the form of an observation questionnaire, validity and practicality. Elearning was validated by 2 experts, consisting of UNP chemistry education graduate students while the test was conducted by chemistry teachers and students. The validity and practicality of the data were analyzed using the Aiken's V technique. Based on the results of the study, it is known that the average Aiken V (V) index of validity is 0.8 with the high validity category, the average Aiken V (V) index of teacher practice tests is 0.81 with high practicality. category and the average Aiken V (V) practicality index of students was 0.82 with the high practicality category. Based on the research results, it can be concluded that e-learning based on project based learning model and assisted by zainulteam.id LMS, the topic of salt hydrolysis is valid and practical for learning chemistry in high school.